Life history traits of the critically endangered catfish eutropiichthys vacha (Hamilton 1822) in the Jamuna (Brahmaputra River Distributary) River, Northern Bangladesh - Md. Yeamin Hossain,; Md. Mosaddequr Rahman,,; Md. Abu Sayed Jewel,; Md. Akhtar Hossain,; Ferdous Ahamed,; Anannya Sen Tumpa,; M. Abdallah, Elgorban; Ohtomi, Jun, (Universiti Kebangsaan Malaysia, 2013)
The critically endangered catfish Eutropiichthys vacha (Hamilton 1822) is one of the commercially high nutritional valuable food fish in Asian countries, but the natural populations are seriously decreasing due to high fishing pressure, leading to an alarming condition and deserving of high conservation importance. Our study describes some biological parameters, including sex ratio, length-frequency distribution (LFD), length-weight relationships (LWRs), length-length relationships (LLRs), condition factors (Allometric, KA; Fulton’s, KF; Relative condition, KR; Relative weight, WR) and form factor (a3.0) of E. vacha in the Jamuna (Brahmaputra River distributary) River, northern Bangladesh. A total of 350 specimens ranging from 8.01-16.95 cm TL (total length) and 1.70-30.38 g BW (body weight) were analyzed in this study. Sampling was done using traditional fishing gears during March 2010 to February 2011. The overall sex ratio showed no significant differences from the expected value of 1:1 (χ2=2.57, p>0.05), and there was no significant difference in the LFD between the sexes (p=0.38). The allometric coefficient b for the LWR indicated isometric growth (~3.00) in males and combined sexes, but negative allometric growth (<3.00) in females. The results further indicated that the LLRs were highly correlated (r2 > 0.997; p<0.001). KR showed significant variations (F=65.11; p<0.01) between male and female; whereas, KF was not significantly different between the sexes (p=0.64). Also, WR was significantly different from 100 for both sexes (p<0.01), indicating the imbalance habitat with food availability relative to the presence of predators for E. vacha. The estimated values of a3.0 were as 0.0060, 0.005 and 0.0054 for males, females and combined sexes of E. vacha. This study reported the first complete and comprehensive description of life-history traits for E. vacha from Bangladeshi waters. These results should be useful for the sustainable conservation of this critically endangered fishery in Bangladesh and neighboring countries.